Serum lactate level as a useful predictor of clinical outcome after surgery: an unfulfilled potential? - Cobianchi, Lorenzo; Peloso, Andrea; Filisetti, Claudia; Mojoli, Francesco; Sciutti, Fabio (Journal of Thoracic Disease, 2016)
The worldwide diffusion of point-of-care testing has made it possible to assess blood lactate easy and fast, but the use of blood lactate monitoring for risk assessment in the critically ill patient remains controversial. The different policies between hospitals and departments reflect the controversy regarding the usefulness of the blood sample (1). Lately, interesting papers about blood lactate level as a predictor of clinical outcomes have been published, but if we consider the whole literature scenario we do not have enough data to consider lactate a totally reliable prognostic index, or at least not in all the clinical settings (2-8).